REFORMASI KURIKULUM DAN KESIAPAN GURU DALAM IMPLEMENTASI PEMBELAJARAN DASAR: ANALISIS PERBANDINGAN INDONESIA–SINGAPORE - Wiwin Luqna Hunaida; Dhuha Hadiyansyah; Zaharil An’asy; Amelia Khoirunisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study analyses curriculum reform and teacher readiness in the implementation of basic education in Indonesia and Singapore, focusing on factors that influence curriculum development, the characteristics of the Indonesian Merdeka Curriculum and the Singapore National Curriculum, and the challenges faced by teachers in teaching practice. This study uses a qualitative approach based on literature review supplemented by in-depth interviews with primary school teachers from both countries. The findings of this study indicate significant efforts in Indonesia through the Merdeka Curriculum with an emphasis on flexibility, project-based learning, and strengthening the Pancasila Student Profile. However, its implementation still faces obstacles in the form of low teacher readiness, weak supervision, and limited resources. system, and high teacher readiness thanks to comprehensive training and adequate technological infrastructure. In contrast, Singapore has a standardised curriculum, a robust monitoring system, and highly prepared teachers thanks to comprehensive training and adequate technological infrastructure. However, teachers in Singapore face high work demands and rapid changes in education. The comparison shows that the success of curriculum reform is highly dependent on teacher competence, institutional support systems, and a consistent learning ecosystem from the central level to the school level. These findings emphasise the need to strengthen teacher capacity and school management so that curriculum implementation in Indonesia is more effective and sustainable.